26.2k views
5 votes
Solve the equation for a.

K = 4a + 9ab

a = K(4 + 9b)
a = 4(K + 9b)
a = a equals StartFraction 4 plus 9 b Over K EndFraction equals h.
a = a equals StartFraction K Over 4 plus 9 b EndFraction equals h.

User Glaze
by
5.6k points

2 Answers

5 votes

Answer:

D or a = k/4+9b

a = a equals StartFraction K Over 4 plus 9 b EndFraction equals h.

Explanation:

User Feelfree
by
5.5k points
1 vote

Answer:


\large\boxed{a=(K)/(4+9b)}

Explanation:


K=4a+9ab\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\K=a(4+9b)\qquad\text{divide both sides by}\ (4+9b)\\eq0\\\\(K)/((4+9b))=(a(4+9b))/((4+9b))\\\\(K)/(4+9b)=a

User Jasonslyvia
by
5.9k points